Pengaruh Financial Attitude, Financial Behavior, Dan Financial Knowledge Terhadap Financial Satisfaction - Deddy Darmawan; Ary Satria Pamungkas (Jurnal Manajerial Dan Kewirausahaan, 2019)
The purpose of this research is to analyze the influence of Financial Attitude, Financial Behavior, and Financial Knowledge toward Financial Behavior. The sample of this research is auditor in four biggest public accounting firms in Jakarta. Sample was selected using convenience sampling method amounted to 130 respondents through spreading questionnaire indirectly via online through the Google form section. Data processing techniques using structural equation modeling that helped by SmartPLS.3.2.7 program. The result of this study reveals that Financial Attitude, Financial Behavior, and Financial Knowledge have effects towards Financial Satisfaction.Tujuan dari penelitian ini adalah untuk menguji pengaruh Financial Attitude, Financial Behavior, dan Financial Knowledge terhadap Financial Satisfaction. Sampel pada penelitian ini adalah auditor pada empat kantor akuntan publik terbesar di Jakarta. Sampel dipilih dengan metode convenience sampling yang berjumlah sebanyak 130 responden dengan menyebarkan kuesioner online dengan bantuan Google form. Teknik analisis data yang digunakan adalah structural equation modeling yang dibantu dengan bantuan program SmartPLS.3.2.7. Hasil yang didapat pada penelitian ini menunjukkan bahwa terdapat pengaruh Financial Attitude, Financial Behavior, dan Financial Knowledge terhadap Financial Satisfaction.